EVA and EBITDA: How such Metrics Can Help in the Investment Decision-Making Process - Gaspar Neto, Diogo Teixeira; Brugni, Talles Vianna; Galdi, Fernando Caio; Prates, Juliana Costa Ribeiro (Advances in Scientific and Applied Accounting, 2024)
Objective: EBITDA is the most widely disclosed non-accounting metric in reference forms and tends to be the most used by analysts. However, EVA is little publicized, despite its qualitative superiority and well-founded theoretical framework. Therefore, it was verified whether EBITDA can better explain the stock returns of Brazilian companies listed on B³. Employing two hypothetical portfolios, it was also verified which decision reference is more efficient and delivers a higher shareholder return, whether portfolios based on the companies’ EVA or portfolios based on the companies’ EBITDA. Method: The analysis is based on data from the companies listed on B³ from 2010 to 2022, collected from the Economatica® database. Through panel data regressions the study hypotheses were tested. Two hypothetical portfolios were built based on firms’ EBITDA and EVA, to empirically verify which of the two indicators is the most efficient in terms of generating investors’ returns. Results: Results indicate that EBITDA better explains the firm’s return on the Brazilian stock market than EVA. Conversely, the portfolio built based on EVA obtained a higher return over the period studied. Contributions: A comparative study of the explanatory power of both metrics in Brazil is relevant to the transformation experienced in the Brazilian capital market. Moreover, evaluating the explanatory power between them helps existing and potential investors to make their investment decisions.